Farmer business school: a climate-smart and gender-responsive approach. - International Potato Center (International Potato Center, 2017)
Farmer Business School (FBS) is a participatory action learning process that involves farmer groups' participation in agricultural value chains. As part of capacity strengthen-ing, FBS comprises a series of group-based experiential learning activities over a pro-duction-marketing cycle while interacting with other chain actors and stakeholders.